Pengaruh Supervisi Akademik Dan Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru SMA Di Dumai Selatan - Sukanto, Sukanto; Mahdum, Mahdum; Hadriana, Hadriana (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
The role of the teacher in the world of education is very dominant in achieving the quality of education, this is because the teacher who deals directly with students, so efforts are needed to improve teacher performance. The basic problems that occur related to teacher performance are the factors that influence teacher performance, there are many factors that affect teacher performance, including academic supervision and the leadership style of the school principal are two factors that are assumed to affect teacher performance. It is assumed that the implementation of academic supervision and the implementation of the principal's leadership style have not been maximal, it is assumed that it has influenced the good and bad performance of senior high school teachers in the Dumai Selatan District. This study aims to determine and test 1) The partial effect of academic supervision on teacher performance, 2) The partial effect of the principal's leadership style on teacher performance, and 3) The simultaneous effect of academic supervision and the principal's leadership style on the performance of senior high school teachers in the Dumai Selatan District. This type of research is a field research (Field Research) with a correlation approach which aims to obtain data from the problems studied, the method in this research is ex post facto. The population in this study were 127 teachers who taught in senior high schools in Dumai Selatan District with the total of sample were 97 teachers.The research results obtained in the field show that: (1) there is a positive and significant influence of academic supervision on teacher performance of 14.0% with a t-count value of 3,933 with a t-table value of 1,988 with a significance value of <0.005. (2) there is a positive and significant influence of the principal's leadership style on teacher performance by 13.0% on the basis of a t-count value of 3,762 > t-table value of 1,988 with a significance value of <0.005, (3) there is a positive and significant influence of supervision academic and leadership style of the principal simultaneously on teacher performance by 30.3% with a constant value of 31.371, with an X1 coefficient of 0.324 and an X2 coefficient of 0.601. Based on the results of this analysis, it can be concluded that academic supervision and leadership style of school principals can be used as predictor variables and can determine and influence the performance of senior high school teachers in Dumai Selatan District.